2021
DOI: 10.1002/adsc.202100189
|View full text |Cite
|
Sign up to set email alerts
|

The Trityl‐Cation Mediated Phosphine Oxides Reduction

Abstract: Reduction of phosphine oxides into the corresponding phosphines using PhSiH3 as a reducing agent and Ph3C+[B(C6F5)4]− as an initiator is described. The process is highly efficient, reducing a broad range of secondary and tertiary alkyl and arylphosphines, bearing various functional groups in generally good yields. The reaction is believed to proceed through the generation of a silyl cation, which reaction with the phosphine oxide provides a phosphonium salt, further reduced by the silane to afford the desired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 58 publications
0
27
0
1
Order By: Relevance
“…This result indicates that phosphorus species in the reaction medium precipitate together with dark/black solid. In order to examine whether these phosphorus species can be phosphine oxides, the oxide form of 1c ( 1c′ ) was synthesized according to literature method [37] and reacted with both Pd (II) (K 2 PdCl 4 ) and Pd(0) species (reduced with NaBH 4 ) in EtOH/H 2 O mixture at room temperature. The 31 P NMR analyses of the reaction medium of these experiments have revealed that the peak of phosphine oxide in 31 P NMR spectrum remained with very strong peak intensity (Figure S23).…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that phosphorus species in the reaction medium precipitate together with dark/black solid. In order to examine whether these phosphorus species can be phosphine oxides, the oxide form of 1c ( 1c′ ) was synthesized according to literature method [37] and reacted with both Pd (II) (K 2 PdCl 4 ) and Pd(0) species (reduced with NaBH 4 ) in EtOH/H 2 O mixture at room temperature. The 31 P NMR analyses of the reaction medium of these experiments have revealed that the peak of phosphine oxide in 31 P NMR spectrum remained with very strong peak intensity (Figure S23).…”
Section: Resultsmentioning
confidence: 99%
“… BINAP is well suited for this purpose as it is moderately prone to oxidation and readily replaces the diolefin at room temperature. After recording the 31 P NMR spectrum of the free ( R )-BINAP ( 31 P­{ 1 H} NMR in toluene: δ −15.0 ppm) during the first loop, the dinuclear mono-substituted species [(COD)­Rh­(μ-Cl) 2 Rh­(( R )-BINAP)] ( 31 P­{ 1 H} NMR in toluene: δ 50.0 ppm, J RhP = 199.0 Hz) is formed upon addition of the precursor [Rh­(COD)­(μ-Cl)] 2 in a 1:1 ratio (Figure ). The second equivalent of BINAP was added during the third loop, resulting in the formation of the dinuclear, disubstituted species [Rh­(( R )-BINAP)­(μ-Cl)] 2 ( 31 P­{ 1 H} NMR in toluene: δ 49.0 ppm, J RhP = 195.6 Hz). , Due to the undesired oxidation, both complexes disappeared over time, in favor of the mono- and dioxidized BINAP ( 31 P­{ 1 H} NMR in toluene: δ 26.3, −14.7 ppm for mono-oxidized BINAP; δ 27.6 ppm for dioxidized BINAP) …”
Section: Resultsmentioning
confidence: 99%
“…High-field (HF) 31 P NMR spectroscopy is nowadays considered a routine tool for the characterization of a wide range of phosphorus-containing systems, e.g., inorganic, main group, and organometallic complexes, which could be highly air-and moisture-sensitive or only stable in solution for a limited period. Phosphines are powerful ligands in homogeneous catalysis, and many modern developments rely on the use of plentiful variations of these compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We started this project by taking advantage of GAP chemistry [29][30][31][32][33] and derivatives of BINAP and BINOLs, which are probably the most widely used chiral categories in asymmetric synthesis and catalysis. The selection of the simplest GAP group is based on two factors: (1) it is more likely to form chiral aggregates in solutions in THF and water; (2) they are readily available and concise to synthesize.…”
Section: Synthesismentioning
confidence: 99%